Synchronization of Libraries, Archives and Museums (LAM) in Malang City as an Effort to Transfer Information - Astrid Wangsagirindra Pudjastawa; Yudit Perdananto (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
In the information age, libraries, archives, and museums (LAM are inseparable units. There are several reasons why LAM stands alone, but the rapid development has fostered new communication and information on the information side. Technology can be used to unify the work of all these institutions. Synchronized LAM can bridge common goals, although there are differences in collections and policies. This article concludes (1) LAM can be used as a concept in the city of Malang because even though the institutions are different and have different policies, some institutions have the same function and purpose, (2) LAM has various types of collections and policies applied to users of the collection, (3) LAM is a container that provides, manages, and transfers information to users. With the LAM synchronization, it is hoped that the efforts to share cultural information in Malang City can be more efficient and comprehensive so that it can be a way to foster public interest in regional arts and culture.